Analisis Kelayakan Lembar Kerja Peserta Didik Elektronik Berbasis Liveworksheets pada Materi Sistem Pencernaan Kelas V Sekolah Dasar - Dania Putri Rangkuti; Muhaiminah Jalal (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research is a type of Research and Development (R&D) aimed at producing an Electronic Student Worksheet (E-LKPD) based on Liveworksheets on the topic of the human digestive system for fifth-grade students at SDN 114/X Pandan Jaya, Tanjung Jabung Timur Regency. This product was developed to address the lack of interactive teaching materials in IPAS (Science) learning and to align learning with the characteristics of 21st-century learners who are familiar with digital technology. The development model used is ADDIE, which includes five stages: analysis, design, development, implementation, and evaluation. In the analysis stage, it was found that teachers had not yet used student worksheets in the learning process, while students showed high interest in digital learning media. The product was developed in accordance with the curriculum and student characteristics, and then validated by content experts (98.26%), language experts (93.33%), and media experts (84%), all of which fall into the very valid category. The product was then tested on teachers and students. The questionnaire results indicated that the E-LKPD is practical to use, with a practicality score of 98.18% from the teacher and 86% from students. Based on these results, it can be concluded that the Liveworksheets-based E-LKPD is valid, practical, and suitable to be used as an interactive teaching material in IPAS learning for fifth-grade elementary school students.